Caudate Head Ischemic Stroke with Concurrent Tubercular Meningoencephalitis: A Case Report - Filippo Nuti; Giulia Ruocco; Patrizia Pasculli; Maria Rosa Ciardi; Giovanni Fabbrini; Matteo Bologna (Reports, 2025)
Background and Clinical Significance: The pathogenesis of ischemic lesions in tubercular meningoencephalitis remains unclear, as do the best therapeutic strategies during the acute phase and for secondary prevention. Case Presentation: We report on an atypical case of tubercular meningoencephalitis with a concomitant ischemic stroke. The infectious origin of the ischemic lesion was hypothesized due to a discrepancy between clinical and radiological findings. The patient underwent neuroimaging, blood tests, and a lumbar puncture to diagnose tubercular meningoencephalitis. She subsequently started on antitubercular therapy. Despite the initiation of treatment, her neurological condition worsened. A computed tomography revealed hydrocephalus, leading to the placement of an external ventricular shunt. This intervention resulted in a reduction in ventricular size and an overall improvement in her clinical condition. To reduce the risk of death, secondary prophylaxis with cardioaspirin was added to her treatment regimen. Conclusions: This report highlights the diagnostic and therapeutic challenges encountered in managing patients with tubercular meningitis presenting with concomitant ischemic stroke. By elucidating the complexities of this clinical scenario, we emphasize the importance of early recognition, comprehensive evaluation, and multidisciplinary management to optimize patient outcomes.